Effects of soil properties and microbial community composition on ginsenosides accumulation in farmland ginseng - Zhang, Tao; Xu, Zhefeng; Wang, Yibing; Gao, Qiao (Frontiers in Bioengineering and Biotechnology, 2024)
Soil is the material basis of ginseng survival, and revealing the correlation between soil and ginsenoside has far-reaching significance for the sustainable development of ginseng industry. In this study, the content of ginsenosides in 3-year-old ginseng roots, the physicochemical properties of rhizosphere soil and the microbial community composition were studied. The results showed that the contents of total saponins in different months were significantly different. The richness and diversity of soil microbial community decreased with the extension of planting time.The activities of complexed iron, organic matter and protease in soil had significant effects on α-diversity of soil microbial community. Functional gene analysis showed that carbon sequestration, protein translation, nitrogen metabolism, transcription factors and chlorophyll metabolism were the main functions of soil bacterial community. The results of correlation analysis and redundancy analysis showed that pH, available potassium, organic matter, complexed iron, Firmicutes and Acidobacteria were the key factors affecting ginsenoside accumulation. The changes of soil physical and chemical properties affect the abundance of soil microorganism, and the accumulation of ginsenoside in ginseng is affected by soil microorganism. A co-regulatory network of Physicochemical Properties-Microbe-Ginsenoside was established. To provide theoretical support for the cultivation of ginseng.